LEADERSHIP LEGACY AND SUSTAINABLE SCHOOL PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, TEACHER MOTIVATION, AND JOB SATISFACTION - Ardin Sianipar; Aldo Hutagalung; Fransiska Wahyu Ari Susilawati (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study examines how leadership style, organizational culture, teacher motivation, and job satisfaction contribute to leadership legacy and sustainable school performance. The purpose of this study is to synthesize existing research, identify key research gaps, and propose an integrative conceptual framework that supports sustainable educational leadership aligned with Sustainable Development Goal 4 (SDG 4). A systematic literature review (SLR) was conducted following PRISMA guidelines. Articles were retrieved through the Dimensions AI platform, which provides access to major academic databases including Scopus, Emerald Insight, ScienceDirect, SpringerLink, and Google Scholar. The initial search identified 150 studies published between 2015 and 2025. After applying inclusion and exclusion criteria based on the PICOS framework and conducting independent screening by two researchers, 42 articles were selected for final analysis. Inter-coder reliability was assessed using Cohen’s kappa to ensure analytical consistency. The findings reveal three key patterns. First, leadership style—particularly transformational, instructional, and collaborative leadership—plays a central role in shaping leadership legacy and long-term school development. Second, organizational culture functions as an institutional mechanism that preserves leadership values and practices across leadership transitions. Third, teacher motivation and job satisfaction act as mediating factors linking leadership practices with school performance outcomes. This study contributes theoretically by proposing an integrative framework connecting leadership style, organizational culture, teacher motivation, and job satisfaction to leadership legacy and sustainable school performance. Practically, the findings provide insights for policymakers and school leaders seeking to strengthen sustainable educational leadership, particularly within the context of Indonesian secondary education.